Short-Term Price Change in the Steel Industry - Morkre, Morris E. (The Review of Economics and Statistics, 1970)
Although the validity of quoted prices is an important issue and must not be slighted, it is suggested here that there are also other important problems in the steel industry which need to be considered. These problems relate to the various ways the industry can respond to changes in external conditions which are made possible by very close relationships among the large number of products it sells. The purpose of the present article is to indicate the importance of these responses for steel price change analysis and then to develop and test a new kind of price change index which attempts to measure these responses. While the orientation of the present article is perhaps somewhat unfamiliar, it is not new. For example, some of the following can be traced to a suggestive